A representação do amor na escrita poética de Beatriz Brandão, Delfina Benigna e Ildefonsa Láura César - Pereira, Deyvid de Oliveira (2014)
Throughout the history of Western literature , we see to be disseminated a conception of love that will substantiate how this feeling is presented in literary productions Trovadorismo and portrayed in later periods to this aesthetic. From love songs to romantic despair, the theme of love letters has a significant role in de Camoes, Bocage , Cervantes , Tomás Antônio Gonzaga and others. However, despite vast reflections on this subject when we dare to overcome phallocentrism the literary canon and seek the representation given to love the woman writer, we incur in a problematic: the female literary discourse on this topic only has national recognition in modern authors and contemporary . Then there is the question: if love was always present, directly or indirectly, as constant theme in literary productions since ancient times , why it is not studied in the writing of Brazilian female authorship in the period of it formation? Thus, in an attempt to fill this theoretical gap, this research is concerned with reflecting the recurrence of thematic loving female poetic writing in the Brazilian colonial period , in the poems of the Francisca de Assisi Beatriz Brandão , Delfina Benigna da Cunha and Ildefonsa Laura César. In order to understand and even make reflections proposed here , becomes therefore necessary to consider significant issues surrounding the representation of love present in the poems of the authors mentioned above , namely the literary aesthetics to which they are bound ( in most cases , the second neoclassical phase) ; classical influence in poetic production of colonial Brazil ; historical , political and ideological context of Brazil then. The character of historical / literary redemption of this research is intended to embrace a specific field of feminist literary criticism: a reflection and analysis of the texts of female authorship of the Colonial Period . Thus, in addition to proposing a visit to forgotten texts, we hope to promote the increase of critical fortune on these writers and, therefore , we will provide material for further reflection .